Synthesis and characterization of silver /kappa- carrageenan nanoparticles using green methods and evaluation of their antibacterial activities - Elsupikhe, Randa Fawzi (2017)
Nanoscale materials have received extensive attention because their unusual properties that differ significantly from bulk sample of the same material. Nanoparticles are particles with size less than 100 nm which small in diameter, but larger in surface area. Silver nanoparticles (Ag-NPs) are being increasingly used in consumer products such as water purification, household cleaning agents and huge in current many exclusive medical applications such as biological engineering. Synthesis of Ag-NPs has attracted the scientists’ attention in recent years due to the huge advantages and applications of Ag-NPs especially as antimicrobial agent. Chemical methods have been used for the synthesis of Ag-NPs, but these methods have a lot of disadvantages because most of the chemical that have been used for synthesis the nanoparticles are too expensive and toxic, which are responsible for various biological risks. Also, most of the chemical methods for synthesis Ag-NPs are not able to control the size of the NPs. Furthermore, the agglomeration between the nanoparticles lead to bad results in antibacterial application. In this work, the green methods for synthesis Ag-NPs have been used for solving these problems and κ-carrageenan polymer has been used as a stabilizer to prevent this agglomeration. Ag-NPs in κ-carrageenan synthesized by different green methods (stirring method, UV- irradiation ultrasonic-irradiation) at room temperature were developed to prepare and control the size of Ag-NPs. Parameters such as the time of stirring, time of irradiation, ultrasonic amplitude, concentration of AgNO3 and concentration of κ-carrageenan have been optimized. κ-carrageenan was used as an eco-friendly stabilizer and AgNO3as producer. Formation of Ag/κ-carrageenan was determined by the UV–visible spectra, which improved the formation of Ag-NPs by surface plasmon resonance in range 300-450 nm. The FT-IR spectra indicated the presence of κ-carrageenan in capping with Ag-NPs. The XRD analysis showed that the Ag-NPs were of face-centred cubic structure. TEM images illustrated the well dispersed of Ag-NPs with similar particle size. SEM images displayed the change on the surface morphology of the κ-carrageenan and illustrated the shape of the Ag-NPs. EDXRF spectra of Ag-NPs in κ-carrageenan confirmed the presence of elemental compounds without any impurity peak. The antibacterial properties of the synthesized nanoparticles were evaluated using agar diffusion methods. Four species of bacteria were used in this study, including two Gram-positive and two Gram-negative bacteria: Methicillin Resistant Staphylococcus aureus (MRSA), Bacillus subtilis, Pseudomonas aeruginosa and Escherichia coli (E-coli). Optimized parameters in the stirring method for synthesis Ag-NPs were: 48 h of stirring times, 0.2 M of AgNO3and 0.3% κ-carrageenan, which produced, the size and the concentration of Ag-NPs of 32 nm and 0.065 M, respectively. The good condition of UV-irradiation method for synthesis Ag-NPs were 60 min irradiation time, 0.2 M AgNO3and 0.3% κ-carrageenan, which produced, the size of and the concentration Ag-NPs of 14 nm and 0.12 M, respectively. The conditions of the ultrasonic-irradiation method for synthesis Ag-NPs that give the best results were 90 min irradiation time, 0.15 M AgNO3, 0.3 % κ-carrageenan and 60 amplitude, which produced the size and the concentration of Ag-NPs of 1.21 nm and 0.22 M, respectively. All Ag-NPs from the above methods were in spherical shape. The different methods demonstrated different results on anti-bacterial activity, which depended on the size and concentration of Ag-NPs. The stability test by using zeta potential analysis proved the Ag-NPs that synthesized by stirring method, UV-irradiation and ultrasonic irradiation were stable. The comparison between the three methods according to the size and concentration of Ag-NPs and the effect on the bacterial activity showed that, the ultrasonic irradiation synthesis was the best method for synthesis of Ag-NPs because the high yield and with a small size of Ag-NPs which lead to a high effect on the bacterial activity.